PENERAPAN METODE LATIHAN PADA PERMAINAN OUTDOOR UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR DAN KETERAMPILAN SOSIAL (Studi Pada Kelompok B TK Negeri 20 Bengkulu Selatan - Herna Kusairi (DIADIK, 2021)
The objectives of  this research are 1). To describe the application of drill methods in outdoor games to improve rough motoryc movements of students at TK Negeri 20 Bengkulu Selatan; 2) To describe the application of drill methods in outdoor games to improve social relationships of students at TK Negeri 20 Bengkulu Selatan. This research uses Class Action Research (CAR). The subject of this research is 15 students of B group at  TK Negeri 20 Bengkulu Selatan. The collecting data used in this research  is the student observation sheet. The data is analyzed by using mean and t-test. This research shows that 1)   the application of drill methods in outdoor games can  improve rough motoryc movements of students at TK Negeri 20 Bengkulu Selatan; 2)  the application of drill methods in outdoor games can  improve social relationships of students at TK Negeri 20 Bengkulu Selatan